Intra-annual variation and correlations of functional traits in Microcystis and Dolichospermum in Lake Chaohu - Guan, Yue; Zhang, Min; Yang, Zhen; Shi, Xiaoli; Zhao, Xingqing (Ecological indicators, 2020)
•M. aeruginosa and D. flos-aquae were the two dominant cyanobacteria in the lake.•There was no significant temporal variation in cell diameter of M. aeruginosa.•Cell diameter and colony size of D. flos-aquae presented monthly variation.•There was positive relationship between cell diameter, colony size and biomass. Microcystis and Dolichospermum are two major genera of bloom-forming cyanobacteria in Lake Chaohu. However, it is little known the way in which the two cyanobacteria adjust their own morphological and physiological characteristics to maintain their biomass. In the study, the phytoplankton community in Lake Chaohu was investigated monthly from June 2017 to May 2018, and the morphological and physiological characteristics of dominant species were also determined. The results showed that Microcystis aeruginosa and Dolichospermum flos-aquae were the two dominant cyanobacteria species in Lake Chaohu. The ranges of the cell diameter and colony size of M. aeruginosa were small throughout the whole year, but those of D. flos-aquae changed significantly over time and in different regions of the lake. There were significant negative relationship between cell diameter and colony size of D. flos-aquae, which indicated that D. flos-aquae was more dependent on morphological adjustment to adapt environmental changes than M. aeruginosa. The biomass of the two algae increased with increasing cell diameter and colony size, indicating that the two algae might maintain their biomass by regulating their morphology. The photosynthetic activity in the cyanobacteria peaked in summer, late winter and early spring. The consistency of the trends in the photochemical activity and biomass of the two algae indicated that the two algae can adapt to environmental changes by changing their photosynthetic characteristics. These findings will be helpful in improving our understanding of the population dynamics of M. aeruginosa and D. flos-aquae and their environmental adaptation mechanisms in Lake Chaohu.